Literature Standar Dalam Kajian Al-Qur’an: Kitab An-Naba’u al-‘Aẓīm Naẓaratun Jadīdatun fī al-Qur’ān Karya Muhammad Abdullah Darraz - Muhammad Falihul Anam; Rezwandi (LPPM IAI Hasanuddin Pare-Kediri, 2026)
The study of the Qur’an in contemporary tafsir discourse demonstrates a significant methodological evolution. One of the prominent figures in this renewal is Muhammad Abdullah Darraz through his seminal work An-Naba’u al-‘Aẓīm Naẓaratun Jadīdatun fī al-Qur’ān. This article aims to examine Darraz’s exegetical thought and methodology, particularly his use of thematic (maudhu‘i) and rational (bi al-ra’yi) approaches in interpreting the content of Surah al-Baqarah. The study reveals that Darraz was not only a Qur’anic exegete but also a multidisciplinary thinker who integrated ethics, logic, and the concept of i‘jāz (inimitability) into his interpretation. By emphasizing the linguistic miracle and thematic coherence of the Qur’an, Darraz presented a form of tafsir that holds both intellectual and spiritual value. His contribution to modern Qur’anic literature serves as a valuable methodological model that bridges classical scholarship and contemporary challenges.